Elimination of senescent osteoclast progenitors has no effect on the age‐associated loss of bone mass in mice. Issue 3 (17th February 2019) - Kim, Ha‐Neui; Chang, Jianhui; Iyer, Srividhya; Han, Li; Campisi, Judith; Manolagas, Stavros C.; Zhou, Daohong; Almeida, Maria
Abstract: Both an increase in osteoclast and a decrease in osteoblast numbers contribute to skeletal aging. Markers of cellular senescence, including expression of the cyclin inhibitor p16, increase with aging in several bone cell populations. The elimination of p16‐expressing cells in old mice, using the INK‐ATTAC transgene, increases bone mass indicating that senescent cells contribute to skeletal aging. However, the identity of the senescent cells and the extent to which ablation of p16‐expressing cells may prevent skeletal aging remain unknown. Using mice expressing the p16‐3MR transgene, we examined whether elimination of p16‐expressing cells between 12 and 24 months of age could preserve bone mass; and whether elimination of these cells from 20 to 26 months of age could restore bone mass. The activation of the p16‐3MR transgene by ganciclovir (GCV) greatly diminished p16 levels in the brain, liver, and osteoclast progenitors from the bone marrow. The age‐related increase in osteoclastogenic potential of myeloid cells was also abrogated by GCV. However, GCV did not alter p16 levels in osteocytes—the most abundant cell type in bone—and had no effect on the skeletal aging of p16‐3MR mice. These findings indicate that the p16‐3MR transgene does not eliminate senescent osteocytes but it does eliminate senescent osteoclast progenitors and senescent cells in other tissues, as described previously. Elimination of senescent osteoclast progenitors, in and of itself, has no effect on the age‐related loss of bone mass. Hence, other senescent cell types, such as osteocytes, must be the seminal culprits.